Pressure tuning of iron-based superconductor Ca10(Pt3As8) ((Fe0.95Pt0.05)2As2)5. (8th February 2019) - Yin, X; Zhang, C; Mu, G; Hu, T; Zhang, M; Xiao, H
Abstract: Systematic high pressure transport measurements were performed on underdoped Ca10 (Pt3 As8 )((Fe0.95 Pt0.05 )2 As2 )5 single crystal sample. At ambient pressure, the sample shows a metallic behavior at high temperatures and then increases with further decreasing temperature. The resistivity dip, which is associated with metal to semiconductor transition is monotonically suppressed by increasing pressure. In contrast, the superconducting transition temperature first increases with pressure and then decreases with further increasing pressure. Magnetization measurements, which gives the bulk, show the same trend as the one obtained from resistivity measurements. An upward curvature is observed in the temperature dependence of the upper critical field, which suggests the multiband nature of the superconductivity. The constructed temperature–pressure ( T − P ) phase diagram is very similar to the reported temperature-doping ( T − x ) phase diagram, suggesting the similar role played by pressure and chemical doping.